2015
DOI: 10.1179/0960340914z.00000000090
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural effects of the reduction step in reactive consolidation of manganese cobaltite coatings on Crofer 22 APU

Abstract: The microstructural effects of the reduction step in the reactive consolidation of slurry processed Mn 1?5 Co 1?5 O 4 coated Crofer 22 APU were studied using cross-sectional scanning and transmission electron microscopies. Alloy samples were coated with a Mn 1?5 Co 1?5 O 4 slurry and then reduced in moist H 2 based forming gas at 850uC for 4 h. The reduced coating contained particles of MnO with the NaCl structure and Co with the face centred cubic (FCC) structure. The interface exhibited a thin dense chromia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The microstructural development of the coatings from deposition to long term aging at 800 °C in air is summarized schematically in Figure 6. Gambino et al [30] showed that during heat treatment of Mn Based on results in the current study, it is argued that the formation of (Mn,Cr) 3 O 4 is a prerequisite for the formation of the Cr-rich reaction layer. Gambino et al [30] proposed that Cr 2 O 3 is formed first on…”
Section: Microstructural Developmentsupporting
confidence: 51%
See 2 more Smart Citations
“…The microstructural development of the coatings from deposition to long term aging at 800 °C in air is summarized schematically in Figure 6. Gambino et al [30] showed that during heat treatment of Mn Based on results in the current study, it is argued that the formation of (Mn,Cr) 3 O 4 is a prerequisite for the formation of the Cr-rich reaction layer. Gambino et al [30] proposed that Cr 2 O 3 is formed first on…”
Section: Microstructural Developmentsupporting
confidence: 51%
“…The first step is heat treatment in N 2 +H 2 (or equivalent reducing atmosphere) where the spinel oxide decomposes into MnO and Co [29]. The second step is heat treatment in air where the spinel phase is re-formed and densification is promoted by a reactionsintering type mechanism [30,31]. The two-step sintering procedure has in some assessments been estimated to make up approximately 20 % of the total interconnect coating costs [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partial densification of the MCCu coating can be explained by Fe diffusion from the alloy into the coating leading to a volume expansion. Lower quantities of Fe (up to 5 wt.%) have previously been observed in (Mn,Co) 3 O 4 coatings after sintering and were attributed to rapid diffusion of Fe in the Co metal that forms when the coating is reduced during the first heat treatment step in N 2 -H 2 [32,33]. Here, Cu in the MCCu coating will also be reduced to its metallic state during heat treatment in N 2 -H 2 .…”
Section: Characterization Of As-prepared Coatingsmentioning
confidence: 84%
“…The average reaction layer thickness was determined to 5.1±1.5 µm. The uneven thickness may be a result of local differences in composition after the reduction heat treatment procedure, during which the coating first is reduced to MnO and Co, and then re-oxidized to MnCo 2 O 4 [32,33].…”
Section: Samples Oxidized At 900 °Cmentioning
confidence: 99%